2017
DOI: 10.18632/oncotarget.14614
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of NF-κBIZ and related cytokines in age-associated renal fibrosis

Abstract: Chronic inflammation is a major contributor to age-related nephropathic changes, including renal fibrosis. In this study, various experimental paradigms were designed to delineate the role played by NF-?BIZ (also known as I?B?) in age-associated renal fibrosis. Analyses based on RNA-sequencing findings obtained by next generation sequencing (NGS) revealed the upregulations of NF-?BIZ and of IL-6 and MCP-1 (both known to be regulated by NF-?BIZ) during aging. The up-regulation of NF-?BIZ in aged rat kidneys coi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 43 publications
1
11
0
1
Order By: Relevance
“…The NF-κB is extensively expressed in renal glomerular cells and renal tubular epithelial cells. The activation of NF-κB can mediate inflammatory response, promote renal tubular epithelial cells turn into fibroblasts cells, and upregulate the expression of a variety of inflammatory factors and chemokines including IL-6, IL-1β, and TNF-α, which results in the promotion of immune inflammatory reaction and renal tubule interstitial fibrosis [33, 34]. Our results found that UA could activate TLR4/NF-кB signaling pathways and induce EMT of renal tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The NF-κB is extensively expressed in renal glomerular cells and renal tubular epithelial cells. The activation of NF-κB can mediate inflammatory response, promote renal tubular epithelial cells turn into fibroblasts cells, and upregulate the expression of a variety of inflammatory factors and chemokines including IL-6, IL-1β, and TNF-α, which results in the promotion of immune inflammatory reaction and renal tubule interstitial fibrosis [33, 34]. Our results found that UA could activate TLR4/NF-кB signaling pathways and induce EMT of renal tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings are in agreement with the observation that oxidative stress is associated with upregulation of IκBζ. 45 Contrary to IκBζ, activation of NF-κB was not dependent on ROS in colonic epithelial cells, as neither NAC nor DPI inhibited the phosphorylation of NFκB-p65. In accordance with this, we found that chemokine synthesis, in particular IL-8, which expression is under the control of NF-kB, was not inhibited by DPI in colonic epithelial cells co-stimulated by TNFα and IL-17.…”
Section: Discussionmentioning
confidence: 93%
“…However, there are still numerous challenges in relation to fully describing this complex biological process [ 18 ]. It has been recently suggested that aging is associated with progressive ECM accumulation which involves loss of function in several tissues [ 19 - 22 ]. Because kidney is one of the most vulnerable tissues which can be influenced by aging and age-related physiological changes, it also shows time-dependent accumulation of ECM in the glomerulus and interstitial parts followed by fibrosis [ 6 , 23 ].…”
Section: Discussionmentioning
confidence: 99%